Astrocyte Mechano-Activation by High-Rate Overpressure Involves Alterations in Structural and Junctional Proteins - Hlavac, Nora; VandeVord, Pamela J. (Frontiers in Neurology, 2019)
Primary blast neurotrauma represents a unique injury paradigm characterized by high-rate overpressure effects on brain tissue. One major hallmark of blast neurotrauma is glial reactivity, notably prolonged astrocyte activation. This cellular response has been mainly defined in primary blast neurotrauma by increased intermediate filament expression. Because the intermediate filament networks physically interface with transmembrane proteins for junctional support, it was hypothesized that cell junction regulation is altered in the reactive phenotype as well. This would have implications for downstream transcriptional regulation via signal transduction pathways like nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB). Therefore, a custom high-rate overpressure simulator was built for in vitro testing using mechanical conditions based on intracranial pressure measurements in a rat model of blast neurotrauma. Primary rat astrocytes were exposed to isolated high-rate mechanical stimulation to study cell junction dynamics in relation to their mechano-activation. First, a time course for “classical” features of reactivity was devised by evaluation of glial fibrillary acidic protein (GFAP) and proliferating cell nuclear antigen (PCNA) expression. This was followed by gene and protein expression for both gap junction (connexins) and anchoring junction proteins (integrins and cadherins). Signal transduction analysis was carried out by nuclear localization of two molecules, NFκB p65 and mitogen-activated protein kinase p38. Results indicated significant increases in connexin-43 expression and PCNA first at 24 hours post-overpressure (p-values<0.05), followed by structural reactivity (via increased GFAP, p-value<0.05) corresponding to increased anchoring junction dynamics at 48 hours post-overpressure (p-values<0.05). Moreover, increased phosphorylation of focal adhesion kinase was observed in addition to increased nuclear localization of both p65 and p38 (p-value<0.05) during the period of structural reactivity. To evaluate the transcriptional activity of p65 in the nucleus, electrophoretic mobility shift assay was conducted for a binding site on the promoter region for intracellular adhesion molecule-1 (ICAM1), an antagonist of tight junctions. A significant increase in the interaction of nuclear proteins with the NFκB site on the ICAM1 corresponded to increased gene and protein expression of ICAM1 (p-values<0.05). Altogether, these results indicate multiple targets and corresponding signaling pathways which involve cell junction dynamics in the mechano-activation of astrocytes following high-rate overpressure.